Peripheral Inflammation Enhances Microglia Response and Nigral Dopaminergic Cell Death in an in vivo MPTP Model of Parkinson’s Disease - García-Domínguez, Irene; Veselá, Karolina; García-Revilla, Juan; Carrillo-Jiménez, Alejandro; Roca-Ceballos, María Angustias; Santiago, Marti; de Pablos, Rocío M.; Venero, José L. (Frontiers in Cellular Neuroscience, 2018)
The impact of systemic inflammation in nigral dopaminergic cell loss remains unclear. Here, we have investigated the role of peripheral inflammation induced by systemic lipopolysaccharide (LPS) administration in the MPTP-based model of Parkinson’s disease. Brain inflammation, microglia and astroglia activation, disruption of the blood–brain barrier (BBB) and integrity of the nigrostriatal dopaminergic system were evaluated in response to i.p. injection of LPS, MPTP or the combination of both. Our results showed that combinative treatment exacerbates microglia activation and enhances (i) the appearance of galectin-3-positive microglia, recently identified as microglial disease-associated phenotypic marker, (ii) the up-regulation of pro-inflammatory cytokines, (iii) the occurrence of A1 neurotoxic astrocytes, (iv) the breakdown of the BBB, and (v) the loss of dopaminergic neurons in the substantia nigra. Microglia activation was triggered earlier than other degenerative events, suggesting that over-activation of microglia (including different polarization states) may induce dopaminergic neuron loss by itself, initiating the endless cycle of inflammation/degeneration. Our study revitalizes the importance of peripheral inflammation as a potential risk factor for Parkinson’s disease and raises the possibility of using new anti-inflammatory therapies to improve the course of neurodegenerative diseases, including those directly aimed at modulating the deleterious activity of disease-associated microglia.